Evaluation on Tourism Recreation Suitability in Libuo Beach - Naning Saleh; Faizal Kasim; Citra Panigoro (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2019)
This study aims to determine the suitability of recreational tourism in Libuo Beach, District of Paguat, Pohuwato Regency based on biophysical parameters. The research was conducted from January to December 2015. The method used is descriptive method using direct observation and measurement in the field. The data used are primary data obtained from observations and direct measurements in the field includes the parameters depth, type of beach, wide beaches, seabed material, current speed, water transparency, harmful biota, and the availability of fresh water. Analysis travel suitability index is calculated according Yulianda travel (2007). The analysis showed that the three research stations in Libuo Beach are in “appropriate” category (SI) with values ranging between 88-93%, making it feasible as a location for leisure travel. Keywords: tourism; suitability; beach; recreation.